How effective are the first and second doses of HPV vaccine in providing protection against cervical dysplasia?. Issue 1 (January 2018) - Manek, Megha; Truax, Elaina; Russo, Daniel
Abstract : EVIDENCE‐BASED ANSWER : The clinical efficacy of 1 and 2 doses of bivalent vaccine is similar to that of 3 doses in protecting against human papillomavirus (HPV) infection (SOR: B, post hoc analysis of 2 RCTs). Two doses 6 months apart appear to elicit similar immunogenicity as 3 doses in the short term; however, the data are conflicting on how long the antibody titers remain comparable (SOR: C, heterogenous RCTs of immune response).